GEJALA NUMBNESS EMOSIONAL SEBAGAI DAMPAK TRAUMA DALAM FILM PERAYAAN MATI RASA - Ilhamsyah, Mohammad Firman; Ahmadi, Anas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The trauma of loss is not always shown through a direct emotional overflow, but can appear in the form of emotional numbness or emotional numbness. The film Perayaan Mati Rasa represents this condition through the character Ian who experiences the trauma of loss and shows various behavioral changes and emotional responses. This research aims to analyze the forms of emotional numbness as the impact of the loss trauma experienced by the main character in the film Perayaan Mati Rasa using the perspective of Cathy Caruth's trauma theory. This research uses a qualitative approach with the content analysis method (content analysis). Research data was obtained through observation and documentation techniques on scenes, dialogues, expressions, and visual elements that represent the trauma of loss and emotional numbness in the film. Data is analyzed through the stage of data reduction, data presentation, interpretation, and drawing conclusions by linking research findings to Cathy Caruth's trauma theory. The research results show that emotional numbness in the character of Ian is represented through three main forms, namely a blank stare, minimal response to emotional situations, and suppressed emotions. These three forms show emotional disconnection, difficulty expressing feelings, and a tendency to hide emotions due to the experience of loss that has not been fully processed. The findings of this study show that trauma is not always present in the form of emotional outbursts, but also through flat expression, emotional alienation, and obstacles in emotional communication. Thus, the film Perayaan Mati Rasa represents emotional numbness as the impact of the loss trauma that deeply affects the character's psychological life.